Agroecological green leafy vegetable business models in Kenya: A Report of the assessment of the green leafy vegetable business models in Kiambu Agroecological Living Landscapes (ALL), Kenya - Wanyama, Rosina; Onyango, Kevin; Bolo, Peter; Ndiwa, Aurillia M; Chege, Christine Kiria (2024)
Green leafy vegetables (GLVs) significantly contribute to the livelihoods of households in Kiambu County. The County’s close proximity to Kenya’s capital, Nairobi, provides an opportunity for farming households to access different markets for their produce within the populous city. Moreso, the increasing consumer demand for traditional African vegetables like amaranth and the African nightshade creates an opportunity for households to make additional income and provides job opportunities for both skilled and unskilled women and youth. In the recent past, production of vegetables in Kiambu County has been fluctuating considerably. This is attributed to unfavourable weather conditions coupled with diminishing land area under production among other factors. Despite this, in 2023, Kiambu County still ranked second after Homabay County in production of Kale, and seventh in terms of cabbage production. This implies that opportunities still exist for the County to fully exploit the potential of vegetables. Adoption of sustainable food systems approaches, like agroecology, may help actors in the value chain overcome multiple challenges associated with production, supply, marketing, and even consumption. The objective this study was therefore to; a) assess the challenges and opportunities of integrating agroecological principles (AEPs) in existing business models for GLV value chains, b) diagnose the current agroecological performance for models with potential for upgrading, develop a business model upgrading strategy for the GLV value chain, c) co-create upgraded agroecological business models, and d) conduct a cost benefit assessment of the agroecological transition. To achieve these objectives, a rapid assessment of the GLV value chain was conducted to better understand the existing business models and the actors involved. Results from this study showed that four business models exist in Kiambu County; i) an organic input-based business model where a private company produces organic inputs and sells to farmers, ii) an specialized markets business model where farmers who produce organic vegetables access designated organic food markets through an intermediary, iii) a private processor model where a private processing company buys vegetables from farmers and processes into different products including dried vegetables, and iv) a conventional business model where farmers produce and sell to different markets directly or through middlemen. The first three models were selected for further diagnosis given their potential for agroecological transition. Diagnosis of the selected business models was done using the Business Model Canvas (BMC) and the Business Agroecology Criteria Tool (B-ACT). The BMC was used to understand the business relationship between actors including the customer segments, value propositions, channels and customer relations, income streams, key resources, key activities, as well as key partners and cost structures. The B-ACT was used to assess how the operations and structure of the business models were aligned or misaligned with the agroecological principles. Prior to the implementation of the BMC and B-ACT tools, each model was assessed to understand their strengths, weaknesses, opportunities and threats.